Хaлықaрaлық қaтынaстaр жүйесіндегі Укрaинa (Халықаралық қатынастар және халықаралық құқық сериясы, 2018)
Problems of modern foreign policy of Ukraine, its relationship withthe states in the world. In the early beginning of creation foreign policyof independent Ukraine, its development, formation according to the internationalstandards is reflected in work. The article discusses the impactof foreign policy on the economic development of the state. In addition,in article the comparative analysis of relationship of the state with the differentcountries, including development of the bilateral relations with theRepublic of Kazakhstan is carried out. The article describes the role ofUkraine in the system of international relations and the main Direction offoreign policy of Ukraine.Key words: Kazakhstan, Ukraine, foreign policy, economic policy, internationalorganizations.